They Sought a Land : A Settlement in the Arkansas River Valley, 1840-1870 - Ragsdale, William Oates, 1915- (Book collections on Project MUSE., 1997)
Ragsdale's primary research into county land purchases and sales shows that the community experienced a climax of economic prosperity in 1860, just before the Civil War took men from their homes to serve in the Confederate and Union armies. Letters and oral histories tell how the deprivations of rural life were met; how bushwhackers terrorized defenseless women and children, stole grain stores, and drove off stock; how bitterness lingered between the returning blues and grays; and how the community eventually dispersed into Arkansas's larger developing society. Absorbing to read and rich with colorful detail, this community history is an important story of the settling of the American South.